2017
DOI: 10.1007/978-3-319-60131-1_3
|View full text |Cite
|
Sign up to set email alerts
|

The BigDataEurope Platform – Supporting the Variety Dimension of Big Data

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…During our analysis, we mapped who the authors of the papers references when using a definition for data lakes. We found that James Dixon was the first one to use the term lake in big data context, in a post in its blog in 2010 [20], and he is referenced by ten papers [4], [6], [17], [32], [38], [44], [62], [63], [67], [91]. The first author to reference Dixon's Concept in academic context was O'Leary [63], in a paper published in 2014.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During our analysis, we mapped who the authors of the papers references when using a definition for data lakes. We found that James Dixon was the first one to use the term lake in big data context, in a post in its blog in 2010 [20], and he is referenced by ten papers [4], [6], [17], [32], [38], [44], [62], [63], [67], [91]. The first author to reference Dixon's Concept in academic context was O'Leary [63], in a paper published in 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Table VII lists the tools cited more than once. Of all the tools, Apache Hadoop was the most mentioned, having 37 citations ( [1], [6], [8], [9], [12], [18], [23]- [25], [27], [28], [30], [31], [40], [42]- [44], [47], [48], [50], [52], [55], [61], [65], [67]- [71], [73], [76], [80], [82]- [86], [88]). Hadoop is a platform that allows distributed processing of large data sets in computer clusters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating the space-time information images of the taxpayers with the space-time remote sensing data, Internet data, business data and claims data of the insured in the overall business, based on which, the spatial-temporal data retrieval, space-time data analysis, Product service tracking, insurance fraud and other services. The concept of "Big Data +" will be extended through such aspects as product design, product pricing, product recommendation [16], product tracking service, product claim settlement and anti-fraud so as to broaden the application scenario of big data technology in smart insurance work, integrate data resources, customer needs, From the relationship between the time and spatial relationship analysis of data, provide a variety of visual analysis capabilities to support the visual relationship between these three layouts, large amounts of data into valuable customer information resources [2]. Dig deeper into data resources to identify potential customers and cheat customers.…”
Section: The Collision Between Insurance and Big Datamentioning
confidence: 99%
“…The overall architecture of the platform is divided into seven layers, including data sources, data acquisition and aggregation, data storage and calculation [3], database management layer, data service layer, data analysis layer, integrated application and terminal layer, and to develop corresponding data standards and application specifications and security Management system, the overall structure as shown (see Fig.?? ).…”
Section: Big Data Platform Architecturementioning
confidence: 99%